Renderings of conspiracy in Los muros azules, by Juan Carlos Martelli (Anclajes, 2021)
Juan Carlos Martelli’s novel Los muros azules (1986) plays between the limits of fantasy and espionage to modulate the story of an anti-colonial and anti-capitalist revolution in the Antilles. Our interpretation takes up the theoretical proposal of Fredric Jameson, who articulates a method based on the rewriting of the social production mode as the master code present in the texts. In this article, we address the ideologeme of the conspiracy, a mediating tool that operates in the field of social antagonisms through the configuration of multiple enunciative identities and the breakdown of dominant rationalities. The superposition of discursive matrices in Martellian fiction guides a reflection, systematized around the conspiracy and the device provided by the Jamesonian hermeneutics, which returns time and again to the writing activity and the conflict within modes of production.
Keywords: Juan Carlos Martelli; Fredric Jameson; hermeneutics; espionaje; fantasy